Al-Shumud wa al-Muqawamah fi Qashidat “Sittun ‘Aman” li-Tamim al-Barghuthi: Qira’ah fi Dhaw’ al-Binyawiyyah at-Takwiniyyah/ Steadfastness and Resistance in Tamim Al-Barghouti’s “Sixty Years”: A Genetic Structuralist Reading - Ihsan Zainuddin; Haniah Haniah; Andi Abdul Hamzah (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2026)
This study examines the representation of steadfastness and resistance in Tamim Al-Barghouti’s poem “Sixty Years” through the lens of Lucien Goldmann’s genetic structuralism. Previous studies on Palestinian resistance poetry have predominantly focused on thematic and historical dimensions, with limited attention to the structural relationship between literary form and collective social consciousness. This study addresses that gap by applying key concepts of genetic structuralism—namely worldview, collective subject, and structural homology—as analytical tools. The research employs a qualitative textual approach using close reading and structural analysis. The unit of analysis includes selected stanzas, recurring imagery, and linguistic patterns within the poem. The analytical procedures involve semantic mapping, identification of binary oppositions, and interpretation of temporal structures, followed by linking these textual elements to the Palestinian socio-historical context. The findings reveal that the poem constructs a coherent collective worldview rooted in historical continuity, resistance, and cultural survival. This is reflected in patterns of temporal extension, collective agency, and symbolic inversion, demonstrating a structural homology between the poetic structure and the social structure of Palestinian experience. The study concludes that resistance is not only expressed thematically but is also embedded structurally within the text, affirming the relevance of genetic structuralism in analyzing contemporary resistance literature.تهدف هذه الدراسة إلى تحليل تمثّلات الصمود والمقاومة في قصيدة “ستون عامًا” لتميم البرغوثي في ضوء نظرية البنيوية التكوينية عند لوسيان غولدمان. وقد ركّزت الدراسات السابقة حول شعر المقاومة الفلسطينية غالبًا على الأبعاد الموضوعية والتاريخية، مع إيلاء اهتمام محدود للعلاقة البنيوية بين الشكل الأدبي والوعي الاجتماعي الجمعي. وتسعى هذه الدراسة إلى سدّ هذه الفجوة من خلال توظيف مفاهيم أساسية في البنيوية التكوينية، مثل: رؤية العالم، والفاعل الجمعي، والتماثل البنيوي، بوصفها أدوات تحليلية. تعتمد الدراسة منهجًا نوعيًا قائمًا على التحليل النصي العميق (Close Reading) والتحليل البنيوي، حيث تتمثل وحدة التحليل في مقاطع مختارة من القصيدة، والصور البلاغية المتكررة، والأنماط اللغوية. وتشمل إجراءات التحليل رسم الخرائط الدلالية، وتحديد الثنائيات الضدية، وتحليل البنية الزمنية، ثم ربط هذه العناصر النصية بالسياق الاجتماعي–التاريخي الفلسطيني. وتُظهر النتائج أن القصيدة تبني رؤية عالم جمعية متماسكة قائمة على الاستمرارية التاريخية، والمقاومة، والبقاء الثقافي. ويتجلّى ذلك من خلال أنماط الامتداد الزمني، ومركزية الفاعل الجمعي، والبنى الرمزية القائمة على قلب الدلالات، مما يعكس تماثلًا بنيويًا بين البنية الشعرية والبنية الاجتماعية للتجربة الفلسطينية. وتخلص الدراسة إلى أن المقاومة لا تتجلّى على المستوى الموضوعي فحسب، بل تتجذّر أيضًا في البنية النصية ذاتها، مما يؤكد فاعلية البنيوية التكوينية بوصفها إطارًا منهجيًا لتحليل أدب المقاومة المعاصر.